Associations between ophthalmic conditions and risk of dementia in older adults: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Hwang, Phillip H; Longstreth, WT; Thielke, Stephen; Francis, Courtney E; Carone, Marco; Fitzpatrick, Annette L
Abstract: Background: It remains unclear whether common ophthalmic conditions in older adults, such as age‐related macular degeneration (AMD), diabetic retinopathy (DR), glaucoma, and cataracts, are related to dementia by causing vision loss or serving as markers of underlying neurodegenerative processes, such as Alzheimer's disease (AD). We examined associations between these ophthalmic conditions and risk of dementia, including AD and vascular dementia (VaD). Method: We identified 3, 236 participants without dementia from the Cardiovascular Health Study (CHS) Cognition Study who were aged ≥65 years and underwent cranial MRI. Presence of AMD, DR, glaucoma, and cataracts were based on ICD‐9 and CPT codes from Medicare Part B and CHS medical records. Dementia classification was completed by consensus committee using data from neuropsychiatric tests or by other data for deceased participants or those unable to come into the clinic. Cranial MRIs were used for classification of dementia subtype. AD was determined using the National Institute of Neurological and Communication Disorders and Stroke – Alzheimer's Disease and Related Disorders Association criteria. VaD was determined using the Alzheimer's Disease Diagnostic and Treatment Centers criteria. Cox models with time‐varying exposure and adjustment for demographics, health behaviors and conditions, and ApoE genotype were used to evaluate associations between these four ophthalmic conditions and risk of all‐cause dementia, AD, and VaD. Result: Increased risk of all‐cause dementia and VaD was significantly associated with AMD, DR, and cataracts, while increased risk of AD was significantly associated with AMD and cataracts (Table 1). When accounting for treatment status, glaucoma was significantly associated with increased risk of all‐cause dementia (HR: 1.53; 95% CI: 1.09 – 2.16; p = 0.015), but all other results remained similar. ApoE genotype was a significant effect modifier as only those without an ɛ4 allele were at increased risk for dementia associated with DR (HR: 5.14; 95% CI: 2.63 – 10.05; p<0.0001) and glaucoma (HR: 1.64; 95% CI: 1.13 – 2.39; p = 0.01). Conclusion: AMD, DR, glaucoma, and cataracts were associated with increased risk of dementia, though not all by the same pathways as some were more strongly related to AD, while others were more strongly related to VaD.